2013
DOI: 10.3748/wjg.v19.i43.7804
|View full text |Cite
|
Sign up to set email alerts
|

Is Dor fundoplication optimum after laparoscopic Heller myotomy for achalasia? A meta-analysis

Abstract: Dor fundoplication is not the optimum procedure after LHM for achalasia. We suggest more attention should be paid on quality of life among different fundoplications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This was performed in our patient and even at the 2-year follow-up no dysphagia or symptomatic GER was observed. This is in accordance with several studies that showed that 360 degree fundoplication is not an obstacle to esophageal emptying after laparoscopic Heller's myotomy [13], achieving excellent results in terms of dysphagia, while Nissen fundoplication seems superior to partial fundoplication in preventing postoperative esophageal acid exposure [14].…”
Section: Discussionsupporting
confidence: 92%
“…This was performed in our patient and even at the 2-year follow-up no dysphagia or symptomatic GER was observed. This is in accordance with several studies that showed that 360 degree fundoplication is not an obstacle to esophageal emptying after laparoscopic Heller's myotomy [13], achieving excellent results in terms of dysphagia, while Nissen fundoplication seems superior to partial fundoplication in preventing postoperative esophageal acid exposure [14].…”
Section: Discussionsupporting
confidence: 92%
“…The fundoplication can be used to buttress (anterior/Dor fundoplication) or accentuate (posterior/ Toupet fundoplication) the myotomy, but is also thought [12][13][14]. Unfortunately, many studies demonstrate persistent reflux even in those patients who do have a fundoplication performed, including up to 21 % of patients following Toupet fundoplication and 42 % following a Dor fundoplication [15,16]. Peroral endoscopic myotomy does not include an anti-reflux procedure; thus, significant attention has been paid to the diagnosis, incidence, and management of reflux in order to better compare and contrast it with the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth pointing out that many studies have demonstrated a high incidence of GER when physiologic testing is performed in no antireflux procedure groups: Campos et al [ 1 ] in a systematic review and meta-analysis reported the rate of 41.5% for abnormal reflux when no fundoplication was added compared with 14.5% when one was performed ( p = 0.01); Falkenback et al [ 10 ] in their prospective randomized trial found that postoperative reflux was observed in 100% of the patients who had the myotomy alone vs. 25% of those who had myotomy with Nissen fundoplication; Richards et al [ 3 ] in their prospective randomized trial found that 48% of patients in the myotomy-alone group had abnormal GER postoperatively, while only 9% of patients had abnormal pH studies when myotomy and partial Dor fundoplication were performed. According to the published results, the routine application of fundoplication following laparoscopic Heller myotomy has been recommended as beneficial for protection against postoperative GER [ 1 , 11 ]. The type of fundoplication has been a subject of debate until now.…”
Section: Discussionmentioning
confidence: 99%